Application of Skin Electrical Conductance of Acupuncture Meridians for Ureteral Calculus: A Case Report - Wu-Chou Lin; Yung-Hsiang Chen; Jian-Ming Xu; Der-Cherng Chen; Wen-Chi Chen; Chao-Te Lee (Case Reports in Nephrology)
Renal colic is a common condition seen in the emergency department (ED). Our recent study showed that measures of electrical conductance may be used as supplementary diagnostic methods for patients with acute renal colic. Here, we describe the case of a 30-year-old male subject with a left ureteral calculus who presented with frequency and normal-looking urine. He had already visited the outpatient department, but in vain. Normal urinalysis and nonobstructive urogram were reported at that time. Two days later, he was admitted to the ED because of abdominal pain in the left lower quadrant. The urinalysis did not detect red blood cells. Ultrasonography did not indicate hydronephrosis. The meridian electrical conductance and index of sympathovagal balance were found to be abnormal. High level of electrical conductance on the left bladder meridian was found. An unenhanced helical computed tomography was scheduled to reveal a left ureterovesical stone. Ureteroscopic intervention was later uneventfully performed, and the patient's pain was relieved. The follow-up measurements showed that the meridian parameters had returned to normal one month after treatment. This case suggests that bladder meridian electrical conductance might be used as a supplemental method for ureteral calculus diagnosis.